Usulan Perbaikan Layout Perpustakaan dan Perancangan Sistem Dashboard di Sd Negeri 074 Ayudia Kota Bandung - Anzelin Dwi Alma Julianty; Dewi Rahmawati; Muhammad Reza; Clariesya Kusumawardani; Yuniar Yuniar (Journal of Science, Technology, and Innovation, 2026)
The library of SD Negeri 074 Ayudia Bandung faces limitations in spatial organization, circulation, reading facilities, and manual collection management. This study aims to propose an improved library layout and develop a digital dashboard to enhance spatial efficiency, service quality, and accessibility of library information. The research employed direct field observation and an integrated engineering approach based on the IISE Body of Knowledge, particularly System Design and Engineering, Information Engineering, Facilities Engineering and Energy Management, and Engineering Economic Analysis. Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) were applied to determine functional relationships and develop the proposed layout, while dashboard development addressed administrative and student information needs. The results produced four functional zones: bookshelf area, main reading corner, admin desk, and creativity corner, supported by a systematic shelf coding system. The admin dashboard records 203 books, 162 available books, 41 borrowed books, and 13 active shelves. The student dashboard facilitates book searches by category, title, author, and shelf location. The estimated supporting investment is IDR 6,110,000. The proposed integration is expected to improve library efficiency, user comfort, service quality, and student literacy.